A Study on Pattern of Alleged Rape Cases at SBMC, Barisal - Barek, Abdul (Anwer Khan Modern Medical College Journal, 2011)
Rape is a common social problem having great implication on the Victim, family, Judiciary and state. However it is very difficult to prove the actual rape because it is difficult to establish whether it is a consented sex or actual rape. 176 cases of alleged rape were studied during the period of 2003-2006 at the SBMC, Barisal. Of these, 130 cases had consented sexual intercourse. 46 victims were subjected to rape. Cases include different age groups, their occupations, living areas, time of arrival for medicolegal examination have been studied. Most of the cases were students. An alarming number of victims were subjected to gang rape. Examination and reporting of the cases with have been discussed. Key Words: Alleged Rape; Pattern; Consented Sex; Gang rape DOI: 10.3329/akmmcj.v1i1.7454 Anwer Khan Modern Medical College Journal 2010; 1(1): 15-18